2019
DOI: 10.1016/j.ajoc.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Leber's hereditary optic neuropathy: Shifting our attention to the macula

Abstract: PurposePeripapillary vascular alterations have been classically described as hallmarks of Leber's Hereditary Optic Neuropathy (LHON). We recently demonstrated microvascular pathology involving the macula in patients affected with chronic LHON using optical coherence tomography angiography (OCTA). Macular vascular pathology in acute LHON has not previously been reported.MethodsThe macular superficial vasculature of an asymptomatic carrier and an affected patient with acute LHON, mitochondrial DNA mutation 3460,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…In contrast, the patient's right eye revealed increased perfusion for both temporal and nasal regions relative to both the patient's left eye (l) and the unaffected eye (j) from Asanad and colleagues. 82,83 Consequently, diagnostic work-up commonly follows incidental visual field findings, pertinent family history, or optic atrophy on funduscopic examination. 89 DOA pathophysiology has been suggested to involve a neurodegenerative etiology.…”
Section: Doamentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the patient's right eye revealed increased perfusion for both temporal and nasal regions relative to both the patient's left eye (l) and the unaffected eye (j) from Asanad and colleagues. 82,83 Consequently, diagnostic work-up commonly follows incidental visual field findings, pertinent family history, or optic atrophy on funduscopic examination. 89 DOA pathophysiology has been suggested to involve a neurodegenerative etiology.…”
Section: Doamentioning
confidence: 99%
“…In contrast, the patient’s right eye revealed increased perfusion for both temporal and nasal regions relative to both the patient’s left eye (l) and the unaffected eye (j) from Asanad and colleagues. 82 , 83 …”
Section: Mitochondrial Optic Neuropathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, vessel attrition corresponded with loss of the retinal ganglion cell-inner plexiform layer (RGC-IPL) and preceded thinning of the retinal nerve fiber layer (RNFL) 4 . In addition to the peripapillary vasculature, recent OCTA studies conducted by our laboratory revealed vascular pathology also in the macula for both chronic and acute disease stages of LHON 1, 5. Borrelli et al.…”
Section: Natural History Of Diseasementioning
confidence: 76%
“…Intriguingly, OCTA of the subacute stage showed vascular attrition with marked enlargement of the foveal avascular zone. In contradistinction, the acute stage exhibited increased vascular perfusion with evidence of microangiopathy and vascular telangiectasias 5 . Similar to chronic LHON, these early vascular changes coincided with loss of the PMB,6, 7 which contains the smallest RGC fibers that are the most vulnerable to mitochondrial dysfunction 8, 9.…”
Section: Natural History Of Diseasementioning
confidence: 90%